Strength and conditioning roundtable: Working with novice coaches - Gillham, A.; Doscher, M.; Schofield, G.; Dalrymple, D.; Bird, S.; Newton, H.; Triplett, T. (International Journal of Sports Science and Coaching, 2015)
Coaches learn how to coach in a variety of ways and mentorship has been suggested as a key component in learning to coach, but is also one that is not widely applied or effectively utilized in sport coaching. In sport, mentorship has been considered within the context of coach-to-coach, administrator-to-administrator and coach-to-athlete. Some attention has been paid to considering the specific context of strength and conditioning coaches, but expert level strength and conditioning coaches have yet to have their voices heard. The purpose of this article was to provide a forum for award-winning strength and conditioning coaches working at high school, collegiate and professional competitive levels to discuss their experiences both learning how to coach and their approach to working with novice coaches. The four respondents provided similar answers to each other and answers that are largely supportive of previous work with sport coaches. Despite the similarities, questions within the context of being a strength and conditioning coach remain and some questions for future research are presented. ABSTRACT FROM AUTHOR